THE IMPORTANCE OF NONVERBAL COMMUNICATION TO DEVELOP COMMUNICATIVE COMPETENCE OF PHYSICAL EDUCATION STUDENTS (American Journal of Pedagogical and Educational Research, 2024)
This article describes the nonverbal communication, particularly hand gestures, plays a crucial role in the teaching and learning process within the field of physical education (PE). As physical activities often require clear, concise instructions, hand gestures serve as an essential tool for enhancing understanding, guiding movements, and facilitating interaction between instructors and students. This article examines the significance of hand gestures in PE, highlighting how they complement verbal instructions, reinforce learning outcomes, and promote effective classroom management. The author states that hand gestures, when used strategically, can improve student comprehension and engagement, particularly in dynamic and fast-paced environments such as PE. By providing visual cues and directing attention, hand gestures help students better understand complex motor skills, exercise techniques, and team strategies, leading to improved performance and coordination.